The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/1084602
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Replay Based Automated Robotic Testing for Mobile App

Abstract: Record-replay testing is widely used in mobile app testing as an automated testing method. However, the current record-replay methods are closely dependent on the internal information of the device or app under test. Due to the diversity of mobile devices and system platforms, their practical use is limited. To break this limitation, this paper proposes an entirely black-box learning-replay testing approach by combining robotics and vision technology to achieve a record-replay testing that can support cross-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…White et al [46] proposed a supervised deep learning approach and automatically identified GUI components to improve the coverage of random testing. Xue et al [47] proposed a supervised deep learning approach to assist in performing record-and-replay GUI testing in a mobile or web application. Mozgovoy and Pyshkin [27] used template matching to recognize objects and GUI elements in a screenshot of a mobile game, which allow test assertions to be made against the visual content of the game.…”
Section: Visual Web and Gui Testingmentioning
confidence: 99%
“…White et al [46] proposed a supervised deep learning approach and automatically identified GUI components to improve the coverage of random testing. Xue et al [47] proposed a supervised deep learning approach to assist in performing record-and-replay GUI testing in a mobile or web application. Mozgovoy and Pyshkin [27] used template matching to recognize objects and GUI elements in a screenshot of a mobile game, which allow test assertions to be made against the visual content of the game.…”
Section: Visual Web and Gui Testingmentioning
confidence: 99%
“…Zhang et al 7 proposed a terminable learning model based on deep learning to identify similarities between GUI and recognizable GUI, avoiding redundant test cases and preventing explosion in the number of test cases by merging redundant isomorphic nodes in the GUI model. Xue et al 8 proposed a completely black-box learning-playback testing method that combines robotics and vision technologies to enable cross-device and cross-platform record-playback testing. At this stage, action recognition techniques are mostly used for recognizing human actions, identity authentication and other scenarios.…”
Section: Related Workmentioning
confidence: 99%